Renewable Energy Driven by Le Chatelier's Principle, Enzyme Function, and Non-Additive Contributions to Ion Fluctuations: A Hypothesis in Biomechanical and Nanotechnology Energy Theory - Sergio Manzetti (Journal of Nanotechnology)
The search for green energy sources has populated the research arena with significant emphasis on green electronics, green fuels, and green batteries that reduce waste, emissions, and environmental toxicity. Simultaneously, nanotechnology has developed substantially in the recent years and the emerging area of nanoenergetics has shown impressive discoveries that can aid in the search for alternative and green energies. The use of exotic materials in these fields and even enzymes has led scientists to be able to cross-link biomolecules and nanotechnology circuits, which can be important points in the search of novel energy searches. This paper discusses a biochemical energy-generating unit driven by ion fluctuations and spontaneous enzyme conformational changes. The paper lays also the theoretical thermodynamical foundation of the nanoenergy unit and to exploit the principle of nonadditivity and equilibrium as main forces in driving an energy-generating reaction.